2011
DOI: 10.1007/s13280-011-0174-0
|View full text |Cite
|
Sign up to set email alerts
|

Tree and Shrub Expansion Over the Past 34 Years at the Tree-Line Near Abisko, Sweden

Abstract: Shrubs and trees are expected to expand in the sub-Arctic due to global warming. Our study was conducted in Abisko, sub-arctic Sweden. We recorded the change in coverage of shrub and tree species over a 32-to 34-year period, in three 50 9 50 m plots; in the alpine-tree-line ecotone. The cover of shrubs and trees (\3.5 cm diameter at breast height) were estimated during 2009-2010 and compared with historical documentation from 1976 to 1977. Similarly, all tree stems (C3.5 cm) were noted and positions determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
74
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(90 citation statements)
references
References 38 publications
11
74
1
Order By: Relevance
“…The underlying mechanism in the model is an increase in light attenuation, favouring taller plants to the detriment of the ground vegetation they shade. Shrub expansion and densification has been reported in numerous studies and related to recent warming trends (Kullman 2002;Jia et al 2003;Tømmervik et al 2004;Tape et al 2006;Hedenås et al 2011;Rundqvist et al 2011). A popular hypothesis is that increased microbial activity in warmer soils enhances the availability of nutrients, particularly nitrogen, and that this lends a competitive advantage to shrubs relative to other types of tundra plants (Chapin et al 1995;Tape et al 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The underlying mechanism in the model is an increase in light attenuation, favouring taller plants to the detriment of the ground vegetation they shade. Shrub expansion and densification has been reported in numerous studies and related to recent warming trends (Kullman 2002;Jia et al 2003;Tømmervik et al 2004;Tape et al 2006;Hedenås et al 2011;Rundqvist et al 2011). A popular hypothesis is that increased microbial activity in warmer soils enhances the availability of nutrients, particularly nitrogen, and that this lends a competitive advantage to shrubs relative to other types of tundra plants (Chapin et al 1995;Tape et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Changes in Arctic plant communities may already be taking place in response to warming over recent decades. Important lines of evidence include positive trends in surface greenness and photosynthetic activity inferred from satellite data (Tucker et al 2001;Bunn and Goetz 2006;Bhatt et al 2010;Beck and Goetz 2011), advancement of elevational and latitudinal treelines (Sonesson and Hoogesteger 1983;Kullman 2002;Harsch et al 2009;Van Bogaert et al 2010, 2011, and an increased cover, abundance and stature of shrubs in tundra areas (Kullman 2002;Jia et al 2003;Tømmervik et al 2004;Tape et al 2006;Hedenås et al 2011;Rundqvist et al 2011). Despite numerous local exceptions, the weight of evidence from observational studies suggests that, in general, Arctic vegetation is responding to rising temperatures through increases in productivity, density, cover and stature of vegetation and, in many areas, an increase in woody biomass and the representation of trees and shrubs (Post et al 2009;Callaghan et al 2011;Elmendorf et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…An alternative explanation is that graminoids have increased due to decreased lemming grazing (Virtanen 2000;Hentton and Wallgren 2001 Table 1 Further, we also found that the cover of juniper increased in agreement with findings by Hallinger et al (2010) in the same general location. Rundqvist et al (2011) described, a more complex pattern in which juniper increased in plots with low cover of mountain birch while it decreased in a plot with much higher cover of mountain birch. Our study revealed a different pattern with a positive correlation between the cover of juniper and basal area and cover of mountain birch.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, field studies and remote sensing have revealed a recent increase in altitude of the treeline (e.g., Kullman 2002), and an extension and increased cover of mountain birch forest (Tømmervik et al 2009;Rundqvist et al 2011, this issue). Tømmervik et al (2009) have-based on remote sensing data-estimated that tree biomass has doubled over a 43-year period, within an area of Finnmarksvidda, and Rundqvist et al (2011) have observed an increased density and cover of mountain birch in the treeline over the last three decades, within an area near Abisko village.…”
Section: Introductionmentioning
confidence: 99%
“…1b). The amount added each autumn is comparable to the litterfall in the mountain birch forest, now undergoing warming-induced expansion in Northern Scandinavia (Kullman and Ö berg 2009;Rundqvist et al 2011). The nutrients are gradually released from the litter by leaching and litter decomposition, and the experiment probably better simulates the stimulation of mineralization, as one of the probable effects of enhanced nutrient availability by warming .…”
mentioning
confidence: 90%